PENDEKATAN ABCD UNTUK MENINGKATKAN LITERASI DI MADRASAH - Andriani Samsuri; Nisful Lailatul U.; Nurul Fithrotuz Z; Feren Eki P. H; Ulfa Vadhila (Buletin Abdi Masyarakat, 2021)
The purpose of literacy KKN with the ABCD approach was to help make changes in schools through the preparation of literacy programs or activities to increase reading interest as well as to increase knowledge or insight in madrasah. In addition, this activity was expected to help increase reading interest and literacy culture in madrasah and later, turn Surabaya into a literacy city. Limited resources and low participation in the learning process lead to low literacy of madrasah students. However, efforts to improve the education process are not only left to schools or the government, but other elements of society also need to be involved. This engagement process was not sufficient with the ABCD approach but requires the participation of the parties concerned, with the hope they can independently make these changes in the future. Change can be made through creativity and innovation. In this case, creativity and innovation are absolutely necessary so that the learning process is fun and increases interest in reading and writing.Keywords: Literacy, ABCD Approach, Participation